The benefit of high-performance gradients on echo planar imaging for BOLD-based resting-state functional MRI. (25th November 2020) - Kang, Daehun; Jo, Hang Joon; In, Myung-Ho; Yarach, Uten; Meyer, Nolan K; Bardwell Speltz, Lydia J; Gray, Erin M; Trzasko, Joshua D; Huston III, John; Bernstein, Matt A; Shu, Yunhong
Abstract: Improved gradient performance in an MRI system reduces distortion in echo planar imaging (EPI), which has been a key imaging method for functional studies. A lightweight, low-cryogen compact 3T MRI scanner (C3T) is capable of achieving 80 mT m −1 gradient amplitude with 700 T m −1 s −1 slew rate, in comparison with a conventional whole-body 3T MRI scanner (WB3T, 50 mT m −1 with 200 T m −1 s −1 ). We investigated benefits of the high-performance gradients in a high-spatial-resolution (1.5 mm isotropic) functional MRI study. Reduced echo spacing in the EPI pulse sequence inherently leads to less severe geometric distortion, which provided higher accuracy than with WB3T for registration between EPI and anatomical images. The cortical coverage of C3T datasets was improved by more accurate signal depiction (i.e. less dropout or pile-up). Resting-state functional analysis results showed that greater magnitude and extent in functional connectivity (FC) for the C3T than the WB3T when the selected seed region is susceptible to distortions, while the FC matrix for well-known brain networks showed little difference between the two scanners. This shows that the improved quality in EPI is particularly valuable for studying certain brain regions typically obscured by severe distortion.